Assume that x n = 3 + n + 3 n and S n = x n + 1 ( x n − 3 ) ( x n − n ) , find the value of i = 1 ∑ 1 0 0 S i 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
why isnt the answer matching
Log in to reply
Seems like the admin had modified the question, it is not the actual answer too.
Problem Loading...
Note Loading...
Set Loading...
Let us take S i 2 = x i 2 + 1 ( x i 2 − 3 ) ( x i 2 − i 2 ) , where x i 2 = 3 + i 2 + 3 i 2 = 3 + ( 1 + 3 ) i . This now yields:
S i 2 = 1 + [ ( 1 + 3 ) i + 3 ] [ ( 1 + 3 ) i + 3 ] 2 − ( i + 3 ) [ ( 1 + 3 ) i + 3 ] + 3 i = 3 + 1 3 + 3 ⋅ i = 3 + 1 3 + 3 ⋅ 3 − 1 3 − 1 ⋅ i = 3 − 1 3 − 3 + 2 3 ⋅ i = 3 i
and finally the summation:
Σ i = 1 1 0 0 3 i = 3 ⋅ 2 ( 1 0 0 ) ( 1 0 1 ) = 5 0 5 0 3 .